2017
DOI: 10.1103/physrevlett.119.132503
|View full text |Cite
|
Sign up to set email alerts
|

A Laser Excitation Scheme for Th229m

Abstract: Direct laser excitation of the lowest known nuclear excited state in 229 Th has been a longstanding objective. It is generally assumed that reaching this goal would require a considerably reduced uncertainty of the isomer's excitation energy compared to the presently adopted value of (7.8 ± 0.5) eV. Here we present a direct laser excitation scheme for 229m Th, which circumvents this requirement. The proposed excitation scheme makes use of already existing laser technology and therefore paves the way for nuclea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 43 publications
(47 reference statements)
1
45
0
Order By: Relevance
“…The concept of laser-based conversion-electron Mössbauer spectroscopy (CEMS) was first proposed in 2017 for direct nuclear laser excitation of 229m Th [27]. The central idea of this concept is to perform nuclear laser spectroscopy of neutral 229 Th atoms instead of ions, as usually considered.…”
Section: The Concept Of Laser-based Cemsmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of laser-based conversion-electron Mössbauer spectroscopy (CEMS) was first proposed in 2017 for direct nuclear laser excitation of 229m Th [27]. The central idea of this concept is to perform nuclear laser spectroscopy of neutral 229 Th atoms instead of ions, as usually considered.…”
Section: The Concept Of Laser-based Cemsmentioning
confidence: 99%
“…In Refs. [27,39] it was shown that the number of excited nuclei Nexc of a nuclear two-level system, when resonantly irradiated with a broad-band and low-intensity source of light, can be calculated as a function of excitation time texc via…”
Section: What Is the Expected Absolute Number Of Nuclear Excitations?mentioning
confidence: 99%
See 2 more Smart Citations
“…This opens the possibility for exciting applications such as a very precise nuclear frequency standard [4][5][6] or a nuclear laser [7]. The extremely low energy may render nuclear spectroscopy and even coherent control of the nuclear excitation with vacuum ultraviolet (VUV) lasers possible [8,9]. Moreover, strong coupling of the nuclear transition to the electronic shell in 229 Th ions may allow usage of the outer electrons to excite the nuclear isomeric state with optical lasers in a two-photon electronic bridge (EB) process [10].…”
Section: Introductionmentioning
confidence: 99%